Uso de plasma convalescente em pacientes com COVID-19 - Dal Bó, Andréa Gurgel Batista Leite (Universidade do Vale do Rio dos Sinos, 2023)
This Collective Health doctoral thesis of the Collective Health Graduate Program at the University of Vale do Rio dos Sinos – UNISINOS – aimed to evaluate the prognostic indicators in critically ill patients with SARS-CoV-2 infection, hospitalized in an Intensive Care Unit (ICU) at Virvi Ramos Hospital in Caxias do Sul/RS, treated or not with convalescent plasma for COVID-19 (PCC). In addition, a survival analysis was also performed. This thesis is composed of two articles. The first makes a mini-review on the early use of convalescent plasma for COVID-19 as a potential low-cost treatment for patients in risk groups, especially in countries with little access to antiviral therapies and vaccines. The second article is a retrospective, propensity-matched cohort study of patients hospitalized in the ICU for severe COVID-19 who received PCC transfusion plus standard care, compared with controls who received standard care only. The primary outcome was mortality within 30 days of admission to the ICU. A total of 124 patients (62 in each group) were included. The median age for the entire series was 66 years (IQR: 55-73), and 89 (55.6%) were men. The median time from symptom onset to PCC was 10 days (IQR: 8-13 days). In total, 51 (41.1%) died within 30 days of admission. PCC transfusion was not independently associated with lower 30-day mortality (OR: 0.52, 95% CI: 0.23–1.16; p = 0.11) and also had no impact on mechanical ventilation or same time.
Keywords: Plasma convalescente; Covid-19; SARS-CoV-2; Unidade de Terapia Intensiva; Convalescent plasma; Intensive Care Unit; ACCNPQ::Ciências da Saúde::Saúde Coletiva